The role of ear mites of the genus Raillietia (Acari: Raillietiidae) in otitis of domestic ruminants - Fernando R.A. Ferry; João L.H. Faccini; Tetsuo Inada (Pesquisa Veterinária Brasileira, 2011)
This paper presents a hypothesis on the involvement of species of the genus Raillietia Trouessart in the pathology of parasitic otitis in domestic ruminants. The chelicerae and claws of the tarsi are structures that contribute significantly towards producing primary lesions. The movable digits of the chelicerae accidentally injure the epithelium that lines the ear canal, while the claws of the tarsi perforate the epithelium, allowing the mites to affix themselves while feeding. The lesions in the epithelium caused by the chelicerae and the claws favor multiplication of the bacteria that inhabit the ear canal, resulting in typical cases of otitis.